Impact of Delivery Mode on Breastfeeding Practices: A Prospective Cohort Study - Goel, Meenal; Jaiswal, Chhavi; Maheshwari, Harsh; Chaudhary, G.S.; Tripathi, Janhavi (Indian Journal of Child Health, 2025)
Background: Breastfeeding is crucial for infant health, providing optimal nutrition and immunity. The mode of delivery significantly influences breastfeeding practices, with Normal Vaginal Delivery (NVD) often enabling earlier initiation and exclusivity than Lower Segment Cesarean Section (LSCS). This study examines differences in breastfeeding initiation, exclusivity, and associated challenges between NVD and LSCS mothers at a tertiary healthcare facility. Methods: A prospective observational study was conducted at Government Medical College (GMC) Jalaun over seven months, including 623 mothers (320 NVD, 303 LSCS). Data were collected using a questionnaire on breastfeeding initiation, breastfeeding practices, and challenges at six weeks, 14 weeks, and six months postpartum. Results: Early breastfeeding initiation (in 1st hour) was significantly higher among NVD mothers (81.88%) compared to LSCS mothers (9.24%) (p < 0.01). LSCS mothers exhibited higher pre-lacteal feeding rates (73.60% vs. 12.19%) and reported more breastfeeding challenges, such as latching difficulties (42.24% vs. 24.06%) and low milk supply (43.23% vs. 22.81%) (p < 0.01). Exclusive breastfeeding rates remained consistently higher among NVD mothers across all follow-up points, with significant differences at six weeks, 14 weeks, and six months. Conclusions: The mode of delivery significantly impacts breastfeeding practices, with LSCS presenting greater challenges to early initiation and exclusivity. Tailored breastfeeding support for LSCS mothers, including immediate skin-to-skin contact and early lactation consultations, may help bridge these gaps, ultimately enhancing maternal and infant health outcomes.